Pengetahuan, Sikap, dan Praktik Pemilik Anjing Terkait Rabies di Kabupaten Sukabumi, Jawa Barat (KNOWLEDGE, ATTITUDE, AND PRACTICE STUDY OF DOG OWNERS RELATED TO RABIES IN SUKABUMI DISTRIC, WEST JAVA) - Wicaksono, Ardilasunu; Ilyas, Abdul Zahid; Sudarnika, Etih; Lukman, Denny Widaya; Ridwan, Yusuf (Jurnal Veteriner; Vol 19 No 2 (2018), 2018)
Sukabumi District is one of the districts in West Java Province that has not been rabies-free since there are still reported rabies dog bites and rabies-positive cases in humans. The aim of the study was to measure the knowledge, attitude and practice of dog’s owner towards rabies which will then be useful for designing the appropriate rabies control programs. A total of 141 dog owners were selected as samples/ respondents. Respondents were taken from two sub-districts in Sukabumi District, which were 66 people from Jampang Tengah Sub-district and 75 people from Cisolok Sub-district. The data were taken using structured questionnaire. The result showed that most of respondent’s level of knowledge (51.1%) was in moderate category, meanwhile the respondent’s level of attitude related to rabies control program mostly (69.5%) was in positive category. But the positive attitude was not reflected with their practice towards rabies control program which many of them (63.1%) was in bad category of rabies control practices. From analytical result showed that only one characteristic variablewhich was the information access about rabies that had significant correlation (c2=9.959, p=0.006) towards respondent’s level of knowledge. Furthermore, another result showed that there was a significant relationship between knowledge variable with respondent’s attitude level (p= 0.000, r= 0.275).